wxPython Recipes A Problem - Solution Approach - Driscoll, Mike (Apress, 2018)
Quickly discover solutions to common problems, learn best practices, and understand everything wxPython has to offer. This book is for anyone wanting to learn more about how to use the wxPython desktop GUI toolkit. It assumes some prior knowledge of Python and a general understanding of wxPython or GUI development, and contains more than 50 recipes covering various tasks and aspects of the toolkit. wxPython Recipes guides you step by step. The book takes you through how to create user interfaces in Python, including adding widgets, changing background images, manipulating dialogs, managing data, and much more. Examples target both Python 2.x and 3.x, and cover both wxPython 3.0 and Phoenix, offering a complete collection of ideas to improve your GUI development.